Cover Feature: Circular Dichroism and Isotropy – Polarity Reversal of Ellipticity in Molecular Films of 1, 1'‐Bi‐2‐Naphtol (ChemPhysChem 1/2019). Issue 1 (21st December 2018) - von Weber, Alexander; Hooper, David C.; Jakob, Matthias; Valev, Ventsislav K.; Kartouzian, Aras; Heiz, Ueli
Abstract : The Cover Feature demonstrates the dependence of the circular dichroism of BINOL films on BK7 substrates to the propagation direction of light and on the enantiomer that is used and its evolution with time upon crystallization. One sees the emergence of optically active scattering, which increase as the domains grow, as illustrated by larger cross‐polarization microscopic cut‐outs. More information can be found in the Article by A. von Weber et al onpage 62 in Issue 1, 2019 (DOI:10.1002/cphc.201800950 ).